Pengaruh Motivasi Instrinsik dan Ekstrinsik Terhadap Prestasi Mata Pelajaran Ekonomi - Aini, Qurratul; Mawardi, Mawardi; Rizkiawati, Baiq Yuliana (Universitas Hamzanwadi, 2017)
This study aims to study intrinsic and extrinsic learning motivation towards economic learning achievement of NW high school students. This research is a correlative descriptive research with a sample of 106 students selected using the Simple Random Sampling Technique. Data collection uses questionnaires and Documentation techniques. The collected data was then analyzed by descriptive and inferential statistical techniques. The results showed: 1) the partial intrinsic learning motivation was significantly significant towards economic learning achievement with F count = 14.083, significance (p) <0.05 and contribution of 14.89%; 2) partial extrinsic learning motivation does not challenge significantly on economic learning achievement at NW Pancor High School with a calculated F value = 3.192 and significance (p) of 0.078 p> 0.05 and benefits of 3.8%; 3) intrinsic learning motivation and extrinsic learning motivation together with importance to student learning achievement, with F count = 7.703, significance value (p) <0.05, and contribution of 16.1%.